Fresno County Bar Association's 110th Annual Bar Banquet Held At Elks Lodge - Watkins, Howard::::::::: (1982)
John McGregor receiving plaque from Fresno County Bar Association President Robert Oliver; Doug Jensen on far right 5080 E. Kings Canyon Road, Fresno